1981
DOI: 10.1002/maco.19810320203
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen zum Einfluß des Stahlgefüges auf die stationäre Wasserstoffpermeation

Abstract: Der Einfluß des Gefügezustandes des Eisens und eines niedriglegierten Stahls auf den stationären Wasserstoffdurchtritt wird mit Hilfe der elektrochemischen Permeationsmethode unter Wasserstoffaufnahme aus der Gasphase hci p H 2 = 1 bar im Temperaturbereich von 15 bis 80 °C untersucht. Der Permeationskoeffizient des Wasserstoffs für reines rekristallisiertes Eisen läßt sich durch beschreiben. Verunreinigungen durch Fremdatome und oxidische Einschlüsse sowie eine hohe Gitterfehlerdichte haben im Eisen keinen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 27 publications
1
10
0
1
Order By: Relevance
“…A deformation-induced decrease of the permeability to H 2 gas was reported for a 0.5 wt pct carbon steel [19] cold rolled to 70 pct, whereas a large increase of permeability was observed in cold-worked AISI 4340 steel [35] and in spheroidized steel samples. [22] In studies involving cathodic hydrogen, the permeability of a mild steel was found to be decreased after cold rolling, [24] whereas the permeability of AISI 4130 steel is reported not to depend on deformation.…”
Section: Influence Of Deformation On the Permeability To Hydrogenmentioning
confidence: 95%
See 3 more Smart Citations
“…A deformation-induced decrease of the permeability to H 2 gas was reported for a 0.5 wt pct carbon steel [19] cold rolled to 70 pct, whereas a large increase of permeability was observed in cold-worked AISI 4340 steel [35] and in spheroidized steel samples. [22] In studies involving cathodic hydrogen, the permeability of a mild steel was found to be decreased after cold rolling, [24] whereas the permeability of AISI 4130 steel is reported not to depend on deformation.…”
Section: Influence Of Deformation On the Permeability To Hydrogenmentioning
confidence: 95%
“…The term D eff exhibits the largest value for normalized AISI 4120 steel, in agreement with literature data, which show larger diffusivity values for pearlitic microstructures compared to bainitic or martensitic ones. [19,23,24] This deviation can be accounted for by a smaller density of trap sites (carbide interfaces and dislocations) in pearlite than in bainite.…”
Section: Influence Of Microstructure and Hydrogen Activitymentioning
confidence: 96%
See 2 more Smart Citations
“…Gas phase charging ensures a constant and reliable chemical potential of hydrogen at the input surface [12]. The electrochemical detection technique is according to Devanathan and Stachurski [13] in an experimental arrangement similar to that outlined in [14]. This arrangement consists of two compartments (input cell and detection cell) separated by the steel permeation membrane which has an exposed area of 1.9 cm 2 on both their entry and exit surfaces.…”
Section: Applications: Api 5l X60 Steel As-received (Ar) Conditionmentioning
confidence: 99%